Chinese state-owned enterprises - McGoldrick, Peter Desmond Julian (Trinity College (Dublin, Ireland). Department of Economics, 2005)
The focus of this thesis is an empirical analysis of the process of operational reform and restructuring in Chinese state-owned enterprises, with a view to examining associated effects on performance, as well as the determination of enterprise characteristics that affect the likelihood of enterprises’ gaining state aid. From four sets of questionnaires, covering the years from 1980 to 1994, a data panel was constructed, which is 681 enterprises wide and fifteen years long. These enterprises are located in four different provinces and classified into forty industries. A key feature of the empirical analysis is the marriage of quantitative data with qualitative data. This yields information essential for the estimation of production functions, as well as revealing, otherwise unobserved, information regarding enterprise characteristics. In particular, these refer to the timing a certain operational reform was implemented, or to whether the enterprise received state aid. After a brief outline of the reform process in China, as viewed in the literature, and the provision of details regarding the construction of the dataset and its summary statistics, the empirical analysis begins.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin